Biomechanics and biotensegrity : study method and frequency response of the simplex and 3- bar-SVD tensegrity configurations - Castro Arenas, Cristhian (2016)
Fil: Castro Arenas, Cristhian. Universidad de Buenos Aires. Facultad de Arquitectura Diseño y Urbanismo. Instituto de la Espacialidad Humana. Centro Laboratorio de Morfología; Argentina